Title: A Qualitative Systematic Review of Parental Perceptions, Motivators, and Barriers to Management of Childhood Obesity - Musa S; Al-Dahshan A; Kehyayan V (Diabetes, Metabolic Syndrome and Obesity)
Sarah Musa,1 Ayman Al-Dahshan,2 Vahe Kehyayan3 1Department of Preventative Health, Primary Health Care Corporation, Doha, Qatar; 2Preventive Medicine Division, Department of Medicine, Hamad Medical Corporation, Doha, Qatar; 3Department of Healthcare Management, College of Business, University of Doha for Science & Technology, Doha, QatarCorrespondence: Sarah Musa, Email smusa@phcc.gov.qaBackground: Childhood obesity is a global epidemic affecting millions worldwide. Children living with obesity face increased risks of health-related and psychosocial problems extending into adulthood. Parents and carers play a crucial role in cultivating healthy habits in their children. This review aims to synthesize qualitative research on parental perceptions, motivators, and barriers in managing childhood obesity and their views on weight management programs.Methods: This systematic review was performed in accordance with the guidelines established by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. A variety of electronic databases were explored for qualitative studies published between 2006 and 2023. The CASP checklist was employed to assess the quality of the studies. Data extraction and synthesis were carried out utilizing thematic content analysis.Results: The search identified 20 peer-reviewed studies meeting the inclusion criteria. Key themes were mapped into five distinct groups: perceptions, facilitators and barriers influencing the management of childhood obesity, as well as facilitators and barriers to enrolment into a weight management program. Parents often perceived obesity as a temporary condition, genetically determined and believed it should not be considered as a major health concern. Identified facilitators included the restriction of screen time, school involvement, goal setting, and enhanced child-parent communication. Conversely, barriers included lack of child motivation, peer influence, easy access to junk food, as well as parental denial, insufficient knowledge or control and logistical challenges.Conclusion: To tackle childhood obesity, it is essential to adopt a comprehensive strategy that fosters a supportive family environment. Successful initiatives should encompass nutritional education for both parents and children, increase access to healthy food choices, implement home-based programs, and improve the infrastructure that encourages physical activity. Additionally, cultural factors and technological advancements should be considered when designing these interventions.Systematic Review Registration Number: PROSPERO (CRD42024514219).Keywords: obesity, children, parents, barriers